Cosmic ray modulation of infra-red radiation in the atmosphere - Aplin, K; Lockwood, M (Institute of Physics Publishing, 2013)
Cosmic rays produce molecular cluster ions as they pass through the lower atmosphere. Neutral molecular clusters such as dimers and complexes are expected to make a small contribution to the radiative balance, but atmospheric absorption by charged clusters has not hitherto been observed. In an atmospheric experiment, a narrowband thermopile filter radiometer centred on 9.15 μm, an absorption band previously associated with infra-red absorption of molecular cluster ions, was used to monitor changes following events identified by a cosmic ray telescope sensitive to high-energy (>400 MeV) particles, principally muons. The average change in longwave radiation in this absorption band due to molecular cluster ions is 7 mWm-2. The integrated atmospheric energy density for each event is 2 Jm-2, representing an amplification factor of 1012 compared to the estimated energy density of a typical air shower. This absorption is expected to occur continuously and globally, but calculations suggest that it has only a small effect on climate. © 2013 IOP Publishing Ltd.